2022
DOI: 10.1097/icu.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

The case for standalone micro-invasive glaucoma surgery: rethinking the role of surgery in the glaucoma treatment paradigm

Abstract: Purpose of reviewTo highlight progress in glaucoma therapy challenging the traditional medication-first approach and present evidence supporting early standalone surgery in the era of micro-invasive glaucoma surgery (MIGS).Recent findingsMedical therapy is limited by well documented poor adherence that compromises the quality of intraocular pressure reduction. Results from modern clinical trials demonstrate advantages of selective laser trabeculoplasty and MIGS procedures in terms of both IOP control and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 102 publications
0
9
0
1
Order By: Relevance
“…Designed as safer and more physiologic alternatives to traditional trabeculectomy and tube-shunt procedures, these procedures collectively offer more modest IOP reductions for patients who would benefit from surgery but whose treatment goals may not justify the risk of traditional surgery [ 153 155 ]. Accordingly, the notion of employing surgery earlier in the treatment cascade, rather than saving it as a last resort, has been raised [ 156 , 157 ]. Given that the trabecular meshwork is the primary site of histopathological changes related to elevated IOP [ 158 ], targeting the meshwork early in the disease process is a logical approach, and several studies have suggested a beneficial disease-modifying effect of early intervention that may not be fully explained by IOP reduction alone [ 159 , 160 ].…”
Section: Discussion: Beyond Medications: a Modern Interventional Glau...mentioning
confidence: 99%
See 1 more Smart Citation
“…Designed as safer and more physiologic alternatives to traditional trabeculectomy and tube-shunt procedures, these procedures collectively offer more modest IOP reductions for patients who would benefit from surgery but whose treatment goals may not justify the risk of traditional surgery [ 153 155 ]. Accordingly, the notion of employing surgery earlier in the treatment cascade, rather than saving it as a last resort, has been raised [ 156 , 157 ]. Given that the trabecular meshwork is the primary site of histopathological changes related to elevated IOP [ 158 ], targeting the meshwork early in the disease process is a logical approach, and several studies have suggested a beneficial disease-modifying effect of early intervention that may not be fully explained by IOP reduction alone [ 159 , 160 ].…”
Section: Discussion: Beyond Medications: a Modern Interventional Glau...mentioning
confidence: 99%
“…Various MIGS procedures combined with cataract surgery have been shown to be cost-effective compared to cataract surgery alone [ 128 , 129 , 161 ], and also compared to topical medication therapy. Relatedly, there have been calls to unbundle some glaucoma procedures from the often-required concomitant cataract surgery and allow them as standalone procedures so patients who might benefit have more than a one-moment-in-time opportunity to receive them at the time of cataract surgery [ 156 ].…”
Section: Discussion: Beyond Medications: a Modern Interventional Glau...mentioning
confidence: 99%
“… 132 , 133 Depending on country and clinical context, some procedures are performed as standalone therapy, while others are performed at the time of cataract surgery. 134 …”
Section: Migs Vs Topical Medicationsmentioning
confidence: 99%
“…Many pseudophakic patients would benefit from standalone MIGS surgery, and the options in this setting are limited. 134 …”
Section: Migs Vs Topical Medicationsmentioning
confidence: 99%
“… 1 However, MIGS usage has evolved with a more expansive role in the current treatment paradigm; the possibility for earlier surgical intervention is a common theme in discussions of MIGS. 2 , 3 Concomitant use with cataract surgery has made glaucoma surgery an accepted option for patients with very mild disease, while demonstrated effectiveness for some MIGS has also been shown for standalone use in refractory glaucoma. 4–6 But what about advanced glaucoma?…”
Section: Introductionmentioning
confidence: 99%